A fluctuation-corrected functional of convex Poisson–Boltzmann theory. (13th August 2018) - Blossey, R; Maggs, A C
Abstract: Poisson–Boltzmann theory allows to study soft matter and biophysical systems involving point-like charges of low valencies. The inclusion of fluctuation corrections beyond the mean-field approach typically requires the application of loop expansions around a mean-field solution for the electrostatic potential, or sophisticated variational approaches. Recently, Poisson–Boltzmann theory has been recast, via a Legendre transform, as a mean-field theory involving the dielectric displacement field . In this paper we consider the path integral formulation of this dual theory. Exploiting the transformation between ϕ and, we formulate a dual sine-Gordon field theory in terms of the displacement field and provide a strategy for precise numerical computations of free energies beyond the leading order.